STANDAR PELAYANAN TANGGAP DARURAT BENCANA MELALUI COMMAND CENTER 112 DI BADAN PENANGGULANGAN BENCANA DAERAH KOTA SURABAYA - Ferynda, Olymvya Prisca; Fanida, Eva (Publika, 2023)
There are various emergency events experienced by the community, so that in this case emergency treatment is needed to minimize fatalities and damage to fatal facilities. To get emergency treatment, the community will contact the Regional Apparatus Organization (RAO) related to the type of emergency that exists. Therefore, the 112 Emergency Call Number Service was created, a service that can be used if an emergency occurs by dialing 112. Then, it will connect the caller to the Emergency Call Center (Call Center 112) in the District/City. Likewise, the Regional Disaster Management Agency for the City of Surabaya formed the Command Center 112 service, which was launched on July 26, 2016, as a result of the many emergency incidents previously faced and officers in the related RAO, unable to respond quickly. In this regard, this study aims to explain the standard of disaster emergency response services provided by Command Center 112 at RDMA of Surabaya City. Descriptive qualitative research is the methodology used. In this case, the researcher collected data through various methods, including interviews, field observations, documentation and literature studies. Furthermore, data reduction, data display and data verification are also used in this study along with the conclusions. In this study, source triangulation, technique triangulation and time triangulation were combined as data validity methodologies. This research gives the result that, in terms of the need for emergency response services, Command Center 112 at RDMA of Surabaya City has been running quite well. Keywords: Public Service, Service Standards, Emergency Handling, 112 Command Center Services